Deactivation effects of Tb3+ on Ho3+ emission in fluoroindate glasses for 3.9 μm laser applications. Issue 8 (15th April 2023) - Zhang, Zhi; Cheng, Zhuowei; Wang, Ruicong; Wang, Shunbin; Farrell, Gerald; Jia, Shijie; Wang, Pengfei
Abstract: A series of Ho 3+ /Tb 3+ co-doped fluoroindate glasses with good thermal stability have been synthesized to study the deactivation effects of Tb 3+ on the Ho 3+ : 3.9 μm emission. Efficient 3.9 μm emission enhancement is obtained under excitation by an 888 nm laser diode (LD). The Judd-Ofelt (J-O) intensity parameters and radiative properties are calculated to evaluate the spectroscopic properties. Possible energy transfer processes resulting in emission reinforcement are discussed. A higher spontaneous transition probability and larger peak emission cross section are achieved with the inclusion of Tb 3+ . This analysis supports the conclusion that Ho 3+ /Tb 3+ co-doped fluoroindate glass is a potentially useful laser material for highly efficient 3.9 μm fiber lasers.